2019
DOI: 10.17305/bjbms.2019.4114
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetics: Therapeutic spark in neuropathic pain

Abstract: Optogenetics is an emerging field, which uses light and molecular genetics to manipulate the activity of live cells by expressing light-sensitive proteins. With the discovery of bacteriorhodopsin, a light-sensitive bacterial protein, in 1971 Oesterhelt and Stoeckenius laid the pavement of optogenetics. However, the cross-integration of different disciplines is a little more than a decade old. The toolbox contains fluorescent sensors and optogenetic actuators which enable visualization of signaling events and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
0
3
0
1
Order By: Relevance
“…Simultaneously, a high-speed camera positioned underneath the platform captured images of each step, which were then transmitted to the analysis software (version 10.6, CatWalk XT, Noldus) for further processing. In this study, eight parameters were identified to assess dynamic behaviors relevant to neuropathic pain: (1) Stand: this parameter represents the duration (in seconds) of a paw touching the glass plate; (2) Stand index: it describes the speed at which the paw moves away from the glass plate; (3) Max contact area: it describes the maximum contact area of the paw or leg with the glass plate; (4) Mean print area: it represents the average area of the paw print during locomotion; (5) Mean intensity: this parameter denotes the average intensity value of the running stage; (6) Duty cycle This parameter denotes the average intensity value of the running stage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, a high-speed camera positioned underneath the platform captured images of each step, which were then transmitted to the analysis software (version 10.6, CatWalk XT, Noldus) for further processing. In this study, eight parameters were identified to assess dynamic behaviors relevant to neuropathic pain: (1) Stand: this parameter represents the duration (in seconds) of a paw touching the glass plate; (2) Stand index: it describes the speed at which the paw moves away from the glass plate; (3) Max contact area: it describes the maximum contact area of the paw or leg with the glass plate; (4) Mean print area: it represents the average area of the paw print during locomotion; (5) Mean intensity: this parameter denotes the average intensity value of the running stage; (6) Duty cycle This parameter denotes the average intensity value of the running stage.…”
Section: Methodsmentioning
confidence: 99%
“…Optogenetics, as an interdisciplinary approach, has demonstrated therapeutic potential in NP. However, the limitations of viral vector delivery systems in humans are well-known ( 5 ). Recently, evidence has emerged suggesting that high frequency terahertz (THz) photons directly resonate with molecules, thereby regulating corresponding biological functions.…”
Section: Introductionmentioning
confidence: 99%
“…Точный патогенез данного состояния неизвестен, однако экспериментально установлена возможность воздействия на его периферический и центральный компоненты. В первом случае в качестве терапевтической мишени были рассмотрены ноцицепторы, во втором -желатинозная субстанция [19].…”
Section: неврологияunclassified
“…Neuropathic pain (NP), a complicated disease of the somatosensory nervous system, affects 7%-10% of the general population worldwide [ 1 ]. Patients who are diagnosed with NP will be accompanied with shooting and burning pain and tingling sensation so that their life quality decreases [ 2 ]. At present, the causative factors of NP is underestimated and the management of NP is on challenge [ 1 ].…”
Section: Introductionmentioning
confidence: 99%